Mitos Kecantikan Remaja Perempuan di Kota Denpasar - Yuliani, Desak Made; Kebayantini, Ni Luh Nyoman; Kamajaya, Gede (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2019)
ABSTRACT This research attempts to explain about the beauty myth among teen girls in Denpasar City. Beauty standard any many innovation in the world of beauty appear the beauty myth who affect self confidence every teen girls. This study used the qualitative approach and was analysed by the beauty myth theory from Naomi Wolf. The beauty industry more loved by teen girls because look beautiful can give a lot of benefit in social environment. Appearance according to the beauty standard easily can be realized through innovation in the world of beauty. But they should pay a price that’s relatively expensive and took several risks in the process. In the other side, fake beauty products also interested by teen girls because on sale with cheap price. Every teen girls have a different purpose in beautify themselves. It is not only for boy, but also for themself, social groups and following the trends. Keywords : Beauty Myth, Beauty Standard, Teen Girls